Structural, Electronic and Magnetic Properties of Impurities Defected Graphene/MoS2 Van Der Waals Heterostructure: First-principles Study - Neupane, H. K.; Adhikari, N. P. (Journal of Nepal Physical Society, 2021)
Two-dimensional (2D) pristine and defected van der Waals (vdW) heterostructure (HS) materials open up fortune in nanoelectronic and optoelectronic devices. So, they are compatible for designing in the fields of device applications. In the present work, we studied structural, electronic and magnetic properties of vdW (HS) graphene/MoS2 ((HS)G/MoS2), Nb impurity defect in vdW (HS) graphene/MoS2 (Nb-(HS)G/MoS2), and Tc impurity defect in vdW (HS) graphene/MoS2 (Tc-(HS)G/MoS2) materials by using spin-polarized DFT-D2 method. We examined the structure of these materials, and found that they are stable. Based on band structure analysis, we found that (HS)G/MoS2, Nb-(HS)G/MoS2 and Tc-(HS)G/MoS2 have metallic characteristics. Also, (HS)G/MoS2 and Tc-(HS)G/MoS2 materials have n-type Schottky contact, while Nb-(HS)G/MoS2 material has p-type Schottky contact. To understand the magnetic properties of materials, we have used DoS, IDoS and PDoS calculations. We found that (HS)G/MoS2 is a non-magnetic material, but Nb-(HS)G/MoS2 and Tc-(HS)G/MoS2 are magnetic materials. Magnetic moment of Nb-(HS)G/MoS2 and Tc-(HS)G/MoS2 materials are -0.24 μB/cell and +0.07μB/cell values respectively from DoS/PDoS calculations, and 0.26 μB/cell and 0.08μB/cell values respectively from IDoS calculations. Up-spin and down-spin states of electrons in 2p orbital of C atoms, 3p orbital of S atoms, 4d orbital of Mo atoms, 4d orbital of Tc atom in Tc-(HS)G/MoS2, and 2p orbital of C atoms, 3p orbital of S atoms, 4p & 4d orbitals of Mo atoms, 4p & 4d orbitals of Nb atom in Nb-(HS)G/MoS2 have major contribution for the development of magnetic moment.